Nanocellulose : From Nature to High Performance Tailored Materials - Dufresne, Alain (De Gruyter, 2017)
This specialist monograph provides an overview of the recent research on the fundamental and applied properties of nanoparticles extracted from cellulose, the most abundant polymer on the planet and an ubiquitous essential renewable resource. Given the rapid advances in the field and the high level of interest within the scientific and industrial communities, this revised and updated second edition expands the broad overview of recent research and will be required reading for all those working with nanocellulose in the life sciences and bio-based applications, biological, chemical and agricultural engineering, organic chemistry and materials science. It combines a general introduction to cellulose and basic techniques with more advanced chapters on specific properties, applications and current scientific developments of nanocellulose. The book profits from the author's extensive knowledge of cellulose nanocomposite materials.